2014
DOI: 10.1021/jp5050546
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Catalytic Heterogeneity in Lactate Dehydrogenase by Temperature Jump Infrared Spectroscopy

Abstract: Protein conformational heterogeneity and dynamics are known to play an important role in enzyme catalysis, but their influence has been difficult to observe directly. We have studied the effects of heterogeneity in the catalytic reaction of pig heart lactate dehydrogenase using isotope edited infrared spectroscopy, laser-induced temperature jump relaxation, and kinetic modeling. The isotope edited infrared spectrum reveals the presence of multiple reactive conformations of pyruvate bound to the enzyme, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(105 citation statements)
references
References 39 publications
6
95
4
Order By: Relevance
“…3 In our model shown here, the two binding modes could correspond to the two well-defined substates, basins A and B, while the transition regions could correspond to the inhomogeneous state, basin C. However, in contrast to the experimental results, 3 our model shows that basins A and B can interconvert either directly or by going through a transition region.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…3 In our model shown here, the two binding modes could correspond to the two well-defined substates, basins A and B, while the transition regions could correspond to the inhomogeneous state, basin C. However, in contrast to the experimental results, 3 our model shows that basins A and B can interconvert either directly or by going through a transition region.…”
Section: Resultscontrasting
confidence: 61%
“…Recent experiments have shown that conformational heterogeneity exists in the Michaelis complex of LDH, 13 and the propensity toward the hydride transfer reaction may vary widely among the different substates of the Michaelis complex. However, the relationship between the substates is still elusive, and the detailed structural features of the substates are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of the phLDH·NADH·pyruvate complex, a small IR band representative of the encounter complex species is in fact observed. 11,13 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that the frequency of the C 2 =O stretch is a quantitative monitor of propensity toward catalysis. 1113 Laser-induced temperature jump spectroscopy, employing isotope edited IR and fluorescence monitors of evolving structure, has yielded the kinetic pathway from ligand binding to catalysis. 1316 These studies have led to an unparalleled identification of mechanistically related structure and dynamics within the Michaelis complex of LDH.…”
Section: Introductionmentioning
confidence: 99%
“…6B). Variability in free energy barriers caused by multiple molecular states has precedent in studies of ligand binding and catalysis, where differences between protein conformational substates and their relative stabilities are thought to cause variations in the activation energy of different pathways (53)(54)(55)(56)(57)(58). The idea of multiple parallel routes for a single reaction is analogous to the welldocumented concept of multiple protein folding pathways (55,56,59).…”
Section: Discussionmentioning
confidence: 99%